Properties of Upgraded Bio-oil from Pyrolysis of Waste Corn Cobs - Abatyough, Michael Terungwa; Ajibola, Victor Olatunji; Agbaji, Edith Bolanle; Yashim, Zakka Israila (Journal of Sustainability and Environmental Management, 2022)
Technologies for conversion of waste solid materials to liquid fuel and bio-crude oil have been researched widely for the production of renewable energy as substitute to fossil fuel oil. However, ash composition of biomass affects the pyrolysis process and the bio-crude oil product has unsatisfactory properties compared to conventional petroleum oil, such as, low heating value, high viscosity, corrosiveness, and the presence of oxygenated compound which causes bio oil ageing. This paper investigated the total waste materials; corn cobs and paper sludge obtained in municipal areas of Abuja, Nigeria, employed in pyrolysis of demineralized corn cobs and the upgrade of crude bio oil via thermal cracking using zeolite prepared from waste paper sludge, with expectation to improve bio oil properties. Demineralization of corn cob removed most of the ash content of biomass allowing for pyrolysis process. The prepared zeolite with mesoporous cage-like crystals analyzed using SEM was able to effectively catalyze thermal cracking of the crude bio oil and reduce the quantity of less desired high molecular weight oxygenated compounds. The bio oil chemical composition obtained from GC-MS analysis indicated the bio oil consisted of oxygenated compounds and hydrocarbons such as aliphatic hydrocarbons (28.768%), alcohols (-0.001%), amines (10.472%), carboxylic acids (0.144), phenols (0.047%), and esters (60.57 %), which significantly influenced the bio oil properties. The physical and chemical properties of the corn cob bio oil was determined for density (0.852 ± 0.03), viscosity (1.66 ± 0.01), cloud point (-34.0 ± 0.02) and calorific value (30.9 ± 0.01). With the exception of Flash point (58 ± 0.01) and acid value (13.1 ± 0.03). In comparison, the produced bio oil had properties likened to petroleum fraction of conventional gasoline than diesel. In conclusion, pyrolysis of corn cob and upgrade of the crude bio oil using prepared zeolite was found as a promising process in improving bio oil quality. The pyrolysis study has potential in the management of environmental wastes to help resolve the challenge of solid waste disposal.